(untitled) (Research, Society and Development, 2025)
The objective of the present study is to understand how the context of use influences the psychedelic experience and the therapeutic potential of Ayahuasca. To this end an integrative literature review was carried out. A search for the descriptors Banisteriopsis, "Ayahuasca" and "Daime" was carried out in the following databases: Scientific Eletronic Library (Scielo); Medical Publisher (PUBMED); Latin American and Caribbean Health Sciences Literature (LILACS). As a result, a total sample of 146 articles was obtained. After applying the inclusion and exclusion criteria, the total sample was 11 articles. The sample was methodologically heterogeneous and allowed us to observe the relevance of the concepts of set and setting as articulating the context of Ayahuasca use from various points of view. The discussion of the data highlights the importance of psychosocial factors which allow the intervention to be extended beyond the neurochemical agent, and finally, the need to carry out new studies with experimental approaches.